Civil rights movement in America : Presidents John F. Kennedy and Lyndon B. Johnson's response to the Black Movement - "Gaikwad, Deepak S" (New Delhi, 1987)
This book deals with civil rights movement in America
Keywords: Civil rights movement United States America